Rhizoctonia Aerial Blight - a Destructive Nursery Disease and its Management - Mehrotra, M. D. (Indian Forester, 1998)
The paper records for the first time the occurrence ofleafblight. a new disease of Cassia fistula Linn.. Bauhinia variegata Linn.. Dalbergia sissoo Roxb. and Populus deltoides Marsh caused by Rhizoctonia solani Khun anamorph of Thanatephorus cucumeris (Frank) Donk in the nurseries in Western Uttar Pradesh. Of the three morphologically different biotypes of the fungus found on diseased plants. one formed typical dark brown sclerotia. the other produced micro-sclerotia. while the third did not produce sclerotia. The disease caused blighting and webbing ofleaves by the fungal hyphae running over the infected aerial parts and forming cobweb like structure. Stromatoid aggregates developed on the surface of infected leaves and clusters of hyphae formed at the base of the petiole or petiolule. The disease caused premature defoliation and group infection of seedlings due to lateral spread of the disease through contact of the overlapping foliage of the adjoining seedlings. Epidemiology of the disease. mode of infection and extent of damage to the seedling crop are described and measures for management of the disease outlined.